Synthetic and spectrometric studies of benzodioxepinone derivatives - Gelebe, Aifheli Carlson (Rhodes University, Faculty of Science, Department of Chemistry, 1995)
An extensive range of oxygen and sulphur substituted benzodiazepine analogues has been synthesised via Baeyer-Villiger and Schmidt reactions of specially prepared flavanone and N-acetyl-4-quinolone precursors. Alternative, cyclisation routes have also been used to prepare some of these compounds. Ring-opening reactions of 1,5-benzodioxepinones have been investigated and a detailed kinetic-mechanistic study of the Baeyer-Villiger reaction of flavanones has been carried out using 1 H NMR spectroscopy to explain the observed regiochemistry of oxygen insertion. The electron-impact mass spectrometric fragmentation patterns of series of 4-aryl-l ,5-benzoxathiepinones, 3-aryl-4, I-benzoxathiepinones and 3-aryl-4,1-benzoxathiepines have been studied using a combination of low-resolution, highresolution and metastable-peak analyses. The 170 NMR spectroscopic properties of various oxygenated analogues have also been studied. The binding affinities of selected benzodiazepine analogues for rat brain benzodiazepine receptors have been evaluated using a radioreceptor assay technique; at certain concentrations, some of test compounds exhibited remarkable potentiation of diazepam binding, others the ability to displace diazepam from benzodiazepine receptors. A conformational analysis of the 7-membered ring systems has been undertaken, using lH NMR spectroscopic, computer modelling and x-ray crystallographic techniques, and certain conformational preferences have been identified.
Keywords: Benzodiazepines -- Research; Flavonoids -- Research